Analisis Resepsi Imperialisme Budaya Dalam Film Seri Korea - Aditya Dwi Rachmad; Aditya Dwi Putra Bhakti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
This study aims to identify and describe the reception of Korean cultural imperialism through traditional games in the Squid Game movie series. This study uses a constructivist paradigm with a qualitative descriptive approach and Focus Group Discussion (FGD) as the data collection method. The subjects studied were 6 informants from followers of the Twitter account @kdrama_menfess who were selected purposively; the study scope was limited to the chosen informants who only come from Javanese culture. Secondary data from this study includes six scenes of traditional games in the Squid Game series and various data sources relevant to the topic of the study. The study used Stuart Hall's analysis theory, which focuses on the encoding-decoding process of the audience. This study found that the audience's attitude in accepting Korean culture was influenced by Korean media consumption activities, fondness for new things from Korea, and social environment. The movie series is an effective medium to create cultural imperialism, but the informants' openness in accepting foreign cultures is a strength for South Korea in building cultural imperialism through series films. So that Korean fans do not feel the impact of Korean cultural imperialism.